Happiness in Yu Sheng. - Poh, Vanessa Yan Ling. (2013)
Yu Sheng is a raw fish salad that consists of slices of raw fish with a variety of vegetables of different colors. It is considered an important dish to the Chinese and is usually consumed during Chinese New Year where people gather around the table and toss the ingredients with shouts of ‘Lo Hei’ and other auspicious wishes.